2010
DOI: 10.1007/s00134-010-1795-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of acetazolamide for reversal of metabolic alkalosis in weaning COPD patients from mechanical ventilation

Abstract: ACET used at the dosage of 500 mg per day reduces metabolic alkalosis but has no benefit in terms of improving PaCO(2) or respiratory parameters in weaning COPD patients from mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 12 publications
1
40
0
1
Order By: Relevance
“…During the weaning process, β 2 -agonists or furosemide was administered by attending physicians as indicated. In our ICU, the criteria for extubation were also standardized in a written protocol detailed elsewhere [10]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the weaning process, β 2 -agonists or furosemide was administered by attending physicians as indicated. In our ICU, the criteria for extubation were also standardized in a written protocol detailed elsewhere [10]. …”
Section: Methodsmentioning
confidence: 99%
“…It has been established that a single 500-mg daily dose of ACET reverses metabolic alkalosis over 72 hours in intubated patients with COPD or asthma as effectively as multiple doses of 250 mg [9]. However, a recent study has shown that ACET administration at a daily dose of 500 mg during the weaning period of COPD patients with mixed or pure metabolic alkalosis only moderately diminishes serum HCO 3 - levels, without changing either partial pressure of carbon dioxide (PaCO 2 ) levels or minute ventilation [10]. The lack of effectiveness of ACET on respiratory mechanics could be due to alterations in ACET pharmacodynamics [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Faisy et al found that a single intravenous dose of acetazolamide (500 mg daily) effectively reduced serum bicarbonate values in patients with metabolic alkalosis, but did not improve PaCO 2 or respiratory parameters such that COPD patients could be more rapidly weaned from mechanical ventilation. 7 Mazur et al found that a single 500-mg intravenous dose of acetazolamide was as effective as multiple 250 mg doses in reversing non-chlorideresponsive metabolic alkaloses in mechanically ventilated asthma/ COPD patients, but they did not specifically assess clinical end points. 8 This latter study argues for less aggressive treatment with acetazolamide, which, in turn, would lessen the occurrence of electrolyte disorders such as hyperchloremic, hypokalemic metabolic alkalosis.…”
Section: Metabolic Alkalosismentioning
confidence: 98%
“…In summary, we found that this recent study (1), confirms the results of two retrospective, case-control studies (3,7) and one randomized clinical trial (8) published on the same subject. The conclusions of all these studies (1,3,7,8) were in severe exacerbation of COPD requiring intensive care admission and invasive MV, metabolic alkalosis occurs frequently in this group of patients who frequently receive therapies for cardiac and respiratory failures (steroids, diuretics, etc.). Moreover, these studies suggest that systemic ACET therapy in this specific condition is not helpful to reduce the duration of MV and to make the weaning process easier.…”
mentioning
confidence: 99%